Pengaruh Ukuran Perusahaan, Profitabilitas Dan Kebijakan Hutang Terhadap Nilai Perusahaan (Studi pada Perusahaan Manufaktur Sub Sektor Industri Dasar dan Kimia yang Terdaftar di BEI Tahun 2017-2019) - Aulia Rizki Dewanti; Ronny Malavia Mardani; Nurhidayah Nurhidayah (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to analyze the effect of firm size, profitability and debt policy on firm value. The method used is correlational associative with a quantitative approach focused on manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange for the period 2017 to 2019 with a sample of 63 companies. The data used is secondary data . The data analysis technique used is multiple linear regression analysis. The results of this study indicate that there is a positive and significant effect of firm size on firm value, there is a positive and significant effect of profitability on firm value and there is a negative but not significant effect of debt policy on firm value in manufacturing companies in the basic and chemical industry sectors listed on the IDX in 2013. 2017 – 2019.. Keywords: Firm Size, Profitability, Debt Policy, Firm Value.